Financial development and economic growth : evidence from Asian countries / Siti Noor Farah Effera Lerohim - Lerohim, Siti Noor Farah Effera (2014)
Financial development is regarded as a healthy positive sign towards the economic growth in Asian countries. Financial development has a correlated with the economic growth of the countries this study is basically to know what cause can affect the financial development and economic growth in the Asian countries. This study concentrates on the secondary data whereby panel data were used as data collection method. We used stata software in order to getting the result of this research. This research has two (2) models which are first, economic growth as dependent variables and for independent variables are investment share, inflation and financial depth. Second model is financial depth as dependent variables and for independent variable are investment share, inflation and economic growth (GDP).